Write x2 - 8x + 13 = 0 in the form (x - a)2 = b, where a and b are integers. a.)(x - 4)2 = 3 b.) (x - 3)2 = 2 c.)(x - 2)2 = 1 d.
) (x - 1)2 = 4
1 answer:
The answer is <span>a.)(x - 4)2 = 3.
(x - a)</span>² = b can be expressed as:
x² - 2ax + a² = b ⇒ x² - 2ax + a² - b = 0
Our equation is x² - 8x + 13 = 0.
The general formula is x² - 2ax + (a² - b) = 0
Thus:
8x = 2ax and a² - b = 13
Divide both sides of the first equation (8x = 2ax) by x:
8 = 2a ⇒ a = 8 ÷ 2 = 4
Replace a in the second equation (a² - b = 13):
4² - b = 13 ⇒ b = 4² - 13 = 16 - 13 = 3
Now when we have a and b, let's just replace them in the general equation:
(x - a)² = b
(x - 4)² = 3
You might be interested in
$60 -$45= $15
$15/ $60* 100%= 25%
The percent discount is 25%~
M is the slope.
B is the y-intercept
The constant of proportionality is the ratio between two directly proportional quantities.
Answer:
$12.30
Step-by-step explanation:
6% of $205 =
= 0.06 * $205
= $12.30
Answer: $12.30
Answer:
![\sqrt{1549}](https://tex.z-dn.net/?f=%5Csqrt%7B1549%7D)
Step-by-step explanation:
square 18 and square 35 then add together
Answer:
Yes
Step-by-step explanation:
Draw a vertical line on the x value of 1/4
It's just a straight line upwards